Examination of Perovskite Structure CaMnO3-δ with MgO Addition as Oxygen Carrier for Chemical Looping with Oxygen Uncoupling Using Methane and Syngas - Dazheng Jing; Tobias Mattisson; Henrik Leion; Magnus Rydén; Anders Lyngfelt (International Journal of Chemical Engineering)
Perovskite structure oxygen carriers with the general formula CaMnxMg1-xO3-δ were spray-dried and examined in a batch fluidized bed reactor. The CLOU behavior, reactivity towards methane, and syngas were investigated at temperature 900°C to 1050°C. All particles showed CLOU behavior at these temperatures. For experiments with methane, a bed mass corresponding to 57 kg/MW was used in the reactor, and the average CH4 to CO2 conversion was above 97% for most materials. Full syngas conversion was achieved for all materials utilizing a bed mass corresponding to 178 kg/MW. SEM/EDX and XRD confirmed the presence of MgO in the fresh and used samples, indicating that the Mg cation is not incorporated into the perovskite structure and the active compound is likely pure CaMnO3-δ. The very high reactivity with fuel gases, comparable to that of baseline oxygen carriers of NiO, makes these perovskite particles highly interesting for commercial CLC application. Contrary to NiO, oxygen carriers based on CaMnO3-δ have no thermodynamic limitations for methane oxidation to CO2 and H2O, not to mention that the materials are environmentally friendly and can utilize much cheaper raw materials for production. The physical properties, crystalline phases, and morphology information were also determined in this work.